2010
DOI: 10.1002/mrm.22452
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐enhanced MRI of salivary glands and head and neck tumors in living subjects

Abstract: Manganese-enhanced MRI has previously been used for visualization of brain architecture and functional mapping of neural pathways. The present work investigated the potential of manganese-enhanced MRI for noninvasive imaging of salivary glands in living subjects. Marked shortening of T1 was observed in salivary glands of naïve mice (n = 5) 24–48 h after systemic administration of MnCl2 (0.4 mmol/kg, intraperitoneally). Three-dimensional MR microscopy confirmed selective contrast enhancement of salivary gland t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Several studies have measured the T1 in tumors after the injection of MnCl2. The limitation of these studies was the acquisitions of T1 maps in 2D on a limited number of slices through the tumors212223. Only a few studies acquired T1 maps in 3D, with the main drawback of long acquisition times: from 40 min24 to ~2 h25.…”
mentioning
confidence: 99%
“…Several studies have measured the T1 in tumors after the injection of MnCl2. The limitation of these studies was the acquisitions of T1 maps in 2D on a limited number of slices through the tumors212223. Only a few studies acquired T1 maps in 3D, with the main drawback of long acquisition times: from 40 min24 to ~2 h25.…”
mentioning
confidence: 99%
“…36, 37) and metal transporters, the mechanisms involved in Mn 2þ uptake in tumor cells are not well known. Some previous studies have shown that MEMRI can enhance some types of tumors in vivo, such as salivary gland and eye (choroidal) tumors (16,17). In particular, Braun and colleagues showed that the uptake of Mn 2þ by tumors depends on the cellproliferation rate (18).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular Mn 2þ can enter cells through N-methyl-D-aspartate (NMDA) receptors for glutamate (14) and/or voltage-gated calcium channels (15). Previous studies have found that MEMRI is useful for the in vivo visualization of tumors such as those arising from head and neck region (16,17). There are several reports, discussing the factors associated with Mn enhancement and tumor uptake.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several recent studies applying MEMRI to oncology suggest its usefulness for detecting some tumors in preclinical animal models, such as human choroidal melanoma xenografts in athymic rats, 2 optic glioma in a neuroˆbromatosis-1 mouse model, 3 and human head and neck tumors in a mouse xenograft model. 4 However, the basis of tumor enhancement in MEMRI remains poorly deˆned. Our recent report that MEMRI could be used to detect mesothelioma with high expression of Mn-SOD suggested the possible preferential enhancement of tumors overexpressing Mn-SOD by MEMRI.…”
Section: Introductionmentioning
confidence: 99%